Gut Microbiome Modulation and Health Benefits of a Novel Fucoidan Extract from Saccharina latissima: A Double-Blind, Placebo-Controlled Trial - Gissel Garcia; Josanne Soto; Carmen Valenzuela; Mirka Bernal; Jesús Barreto; María de la C. Luzardo; Raminta Kazlauskaite; Neil Waslidge; Charles Bavington; Raúl de Jesús Cano (Microorganisms, 2025)
This randomized, double-blind, placebo-controlled, three-arm clinical trial evaluated the effects of a proprietary bioactive fucoidan-rich extract derived from Saccharina latissima (SLE-F) on gut microbial composition and function in healthy adults. The objective of the study was to assess the potential of SLE-F to beneficially modulate the gut microbiome, with this paper specifically reporting on microbial diversity, taxonomic shifts, and functional pathway outcomes. Ninety-one participants received either a low dose (125 mg), high dose (500 mg), or placebo twice daily for four weeks. The primary endpoint was the microbiome composition assessed via 16S rRNA sequencing (V3–V4 region), with secondary outcomes including surveys, adverse event monitoring, and clinical evaluations. High-dose supplementation resulted in dose-dependent improvements in the microbial diversity; increased abundance of beneficial taxa, including Bifidobacterium, Faecalibacterium, and Lachnospiraceae; and reductions in inflammation-associated taxa, such as Enterobacteriaceae and Pseudomonadota. A functional pathway analysis showed enhancement in short-chain fatty acid biosynthesis and carbohydrate metabolism. The low-dose group showed modest benefits, primarily increasing Bifidobacterium, with limited functional changes. In vitro colonic simulations further demonstrated a dose-dependent increase in short-chain fatty acids and postbiotic metabolite production following SLE-F exposure. SLE-F was well tolerated, with only mild, nonspecific adverse events reported. These findings support the potential of SLE-F as a safe and effective microbiome-modulating agent, warranting further study of the long-term use and synergy with dietary interventions.